Using Blended Disaster Learning Multimedia (BDLM) for Geography Teachers Candidate: Experimental Study on Disaster Preparedness Knowledge - Rima Meilita Sari; Rusmaniah Rusmaniah; Ridhwan Ridhwan (Geosfera Indonesia, 2023)
Blended learning needs supporting components to be able to achieve learning objectives. The use of Blended Disaster Learning Multimedia (BDLM) is used as teaching material to support the blended learning process. The purpose of this study was to determine the effect of using BDLM on knowledge of disaster preparedness. We used a quasi-experimental design using a pretest posttest non-equivalent control group design. Data were analyzed using ANCOVA. Research participants were prospective geography teachers who are participating in the lecture program in the 2021/2022 academic year. To assess the knowledge of disaster preparedness using an essay test that is adapted to disaster preparedness indicators. The results show that BDLM integrated blended learning has an effect on knowledge of disaster preparedness. The experimental group appears to have superior knowledge of disaster preparedness with superiority in all indicators of knowledge of disaster preparedness. There is no significant effect between gender differences, because the treatment does not discriminate between gender. The interaction between BDLM learning and gender has a significant effect due to BDLM is a medium that focuses on learning activities not on the treatment of gender differences. The perceived impact is that using BDLM can increase disaster preparedness knowledge. Therefore it is necessary to apply it to prospective geography teachers more broadly.